Synthesize and characterization of sustainable natural fibers/ conductive polymer composites - KOÇAK, EMİNE DİLARA (My University, 2022)
This work aims to obtain reinforced composites of natural fibers that obtained from their agricultural wastes of and conductive polymers to develop an innovation and alternative materials. By the use of natural fibers contributes to the recycle of agricultural wastes, sustainability and further the resulting composite becomes alternative to the metals. Here, flexible conductive composites were obtained from artichoke(A), banana(B) and luffa(L) stem waste fibers(F) by the in-situ polymerization of 3,4-ethylene dioxythiophene (EDOT), pyrrole, and carbazole in the presence of cerium ammonium nitrate, iron nitrate, and iron chloride. Fibers were coated with the conductive polymers mentioned above by the in-situ chemical(C) polymerization and optimum coating conditions were investigated. Effect of EDOT concentration, oxidant concentration was performed to determine the optimum conditions for AF/PEDOT(C). FT-IR, SEM, thermal analysis supported the formation of composite and from the mechanical measurements, modulus of AF/PEDOT(C) was obtained. The highest conductivity of 12.8 S/cm was obtained from AF/PEDOT(C) composite using FeCl3 as an oxidant. Further polymerization of EDOT by electrochemical(E) method was continued on the AF/PEDOT(C) and the electroactivity of resulting electrochemical composite, AF/PEDOT(C)/PEDOT(E) was characterized accordingly. Detailed characterization showed that to use of this composite as a capacitor, one should use 0.03 M EDOT and 0.9 M FeCl3 for chemical polymerization and then continued by electropolymerization by applying 10 cycles in 0.03 M EDOT. All results showed that AF waste could be converted to the valuable AF/PEDOT(C)/PEDOT(E) conductive composites which is potentially suitable material for several electronic applications as charge storage, biosensor, electronic devices.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; artichoke; luffa; banana; polyethylenedioxythiophene; conductive flexible composite; POTENTIAL REINFORCEMENT; POLYANILINE; POLYPYRROLE; FABRICATION